Finite element model updating - Syed Muhammad, Kashif (IIUM Press, 2011)
In this chapter, Finite Element Model Updating method is discussed. The method constitutes a widely accepted and practiced procedure especially for the solution of direct problems. In such applications, a comparison is made between actual measured results and simulated counterpart. The simulated results are obtained by taking as input the material’s constitutive parameters. The idea is to close the gap between numerical and experimental results with the iterative refining and updating of input material properties, till the time a an acceptable convergence is attained. The present chapter discusses about the use of this iterative procedure with the exploitation of full field data and its related issues.